2015
DOI: 10.1021/acs.joc.5b02345
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrically Substituted and π-Conjugated 2,2′-Bipyridine Derivatives: Synthesis, Spectroscopy, Computation, and Crystallography

Abstract: A new series of monosubstituted styryl- and bistyryl-2,2'-bipyridine luminophores (compounds 16-23) have been synthesized via Horner-Wadsworth-Emmons reaction involving a monophosphonate and donor aromatic aldehydes. In the title chromophores, the amino donors are varied between acyclic and cyclic while the alkoxy donors are varied in terms of their number and position. The absorption maxima of these chromophores shift predominantly due to intramolecular charge transfer (ICT) between different donor and accept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…It has previously been shown that the presence of substituents at 5,5'-positions of 2,2'-bipyridine causes a significant red-shift of the emission maximum akin to that of the protonated ligand [8]. The main interactions in these molecules occur by an intramolecular charge-transfer (ICT) between the donor (D) and acceptor (A) functionalities, thereby tuning the optical properties [9]. The bpy derivatives are very promising candidates as a fluorescent probe, a property that is associated with the orbital energy of the lowest unoccupied molecular orbital (LUMO) of pyridine [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been shown that the presence of substituents at 5,5'-positions of 2,2'-bipyridine causes a significant red-shift of the emission maximum akin to that of the protonated ligand [8]. The main interactions in these molecules occur by an intramolecular charge-transfer (ICT) between the donor (D) and acceptor (A) functionalities, thereby tuning the optical properties [9]. The bpy derivatives are very promising candidates as a fluorescent probe, a property that is associated with the orbital energy of the lowest unoccupied molecular orbital (LUMO) of pyridine [9].…”
Section: Introductionmentioning
confidence: 99%
“…The main interactions in these molecules occur by an intramolecular charge-transfer (ICT) between the donor (D) and acceptor (A) functionalities, thereby tuning the optical properties [9]. The bpy derivatives are very promising candidates as a fluorescent probe, a property that is associated with the orbital energy of the lowest unoccupied molecular orbital (LUMO) of pyridine [9]. As both a σ-donor and π-acceptor ligand, 2,2′-bipyridine derivatives form very stable metal complexes due to the formation of a five-membered ring [10].…”
Section: Introductionmentioning
confidence: 99%
“…26 We have also reported a series of asymmetrically substituted and π-conjugated 2,2′-bipyridine derivatives including their photophysics and computational studies. 27 Last several years, in our laboratory, we have been exploring diverse inorganic and organic systems that can be described as functional materials. 2830 As a part of our recent research on exploring functional materials, we have recently developed interests in fluorescent chemosensors and reported our first success in selective sensing of Fe 3+ ion and IO 4 – ion by a metallocycle host.…”
Section: Introductionmentioning
confidence: 99%
“…We have also performed density functional theory (DFT) calculations to corroborate the UV−visible and ■ RESULTS AND DISCUSSION Synthesis. The 2,6-bis(pyrazolyl)-4-bromomethyl pyridine precursor IK-1 (see Chart 1 for the structural representation of IK-1) 46 and the required appropriate N,N-dialkylated-and pyrrolidine-substituted aldehydes S 1c−7c 26,27 (see Scheme S1, Supporting Information for syntheses and structural drawings of S 1c−7c ) along with their precursors were synthesized according to the literature procedures in good yields (see Schemes S1 and S2 in the Supporting Information). Compound IK-2 (phosphate derivative, see Chart 1) was synthesized by Arbuzov reaction of compound IK-1 with Crystal Structure Description and Discussion.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation